The Price we Pay for a Specialised Society: Do Tax Disputes Require Greater Judicial Specialisation? - Miles, Sarah (Victoria University of Wellington Law Review, 2015)
In recent years, a review of the Judicature Act 1908 and the introduction of the Judicature Modernisation Bill have enlivened the debate over the structure and character of the New Zealand court system. A key issue that the recent review and reforms have brought to the fore is whether greater judicial specialisation is advantageous at the High Court level. This article considers whether tax cases, in particular, warrant greater judicial specialisation. The article draws from experiences of specialised tax adjudication in foreign jurisdictions and evaluates the efficacy of existing specialisation in the New Zealand system, as well as considering whether the nature of tax law lends itself to specialisation. The conclusion is that greater judicial specialisation in respect of tax cases is undesirable.